The Winter Massacre – How Napoleon’s Army Died At Berezina - Empires Reawakened (NC, 2025)
The Winter Massacre – How Napoleon's Army Died at Berezina.
Droits : Vidéo publique YouTube. Droits conservés par le diffuseur.
Keywords: vidéo; youtube; histoire; documentaire; mémoire; Napoléon; Bonaparte; Histoire